‘Listening State?’: exploring citizens’ perceptions of Open Government in Tokayev’s Kazakhstan - Kurmanov, B.; Selteyev, U.; Almaganbetov, A. (Central Asian Survey, VOL. 43, NO. 2, 235-256, 2023)
The Open Government reform has been actively adopted across various non-democratic regimes, including post-Soviet Central Asia. The reform is supposed to bolster responsiveness and transparency through the active use of information communication technologies, and numerous authoritarian countries have recently adopted and deepened the Open Government reform. In this work, we study whether Open Government reform contributes to responsiveness in autocracies using the case of Kazakhstan under Tokayev’s rule (2019–present). We investigate the concept of the ‘Listening State’ recently adopted in Kazakhstan through the analysis of novel primary data. The perceptions of ordinary citizens reveal that the Open Government reform in the country has not led to the realization of its key goal of increased responsiveness. Therefore, we argue that the Open Government reform has serious limitations in achieving its ultimate goal of a better listening state to people’s needs in autocracies.
Keywords: Open Government; government responsiveness; citizen participation; authoritarianism; authoritarian upgrading; Kazakhstan